A myth greater than Zeus: popular perceptions and scholarly realities about the French Revolutionary levée en masse - Wild, Samuel (My University, 2024)
In recent years, there has been an increasing interest in the Levée en Masse, or more accurately, its depiction in history. For years, the Levee has been used as a tool of propaganda and a supporting part of Marxist history on the French Revolution, creating a myth or legend of the Levée en Masse as a spontaneous and patriotic event where the men of France rushed to the republic's defence. However, this has changed as historians both inside and outside France have challenged the myth of the Levée, and by the late 1980s, this myth was only perpetuated by a dwindling number of Marxists. The issue is that this perception of the Levée en Masse has been defeated in academia; the myths of the Levée remain in the popular perception of history thanks to two hundred years of Marxist literature and French Propaganda. This presentation aims to identify and debunk the nationalist legend of the Levée en Masse that has distorted the Popular perception of this pivotal and complex historical event.
Presented on April 19, 2024 at Student Research Day held at MacEwan University in Edmonton, Alberta.
Keywords: levée en masse; French Revolution; nationalism; political rhetoric